Effect of soil steam sterilization on weed seeds. - Castillo-Luna, María del Pilar; Gómez-Gómez, Robin (Agronomía Mesoamericana, 2016)
The objective of this study was to evaluate the effect of soil steam sterilization on the viability of seeds of three weed species. The experiment was carried out in 2014 at the Fabio Baudrit Moreno Experiment Station (EEAFBM) of the University of Costa Rica. Weed seeds of Poa annua, Polygonum hydropiperoides, and Brassica campestris, common in soils used to prepare vegetable nurseries in the high lands of Cartago, were evaluated. Weed seeds were placed at two depths (20 and 40 cm) inside a barrel with soil; temperature at both depths and in different intervals was determined. The experimental design was random blocks with three replicates per species per depth. Temperature was measured when steam emerged on top of the soil column. Soil sterilization continued for thirty minutes and then soil temperature was measured again at both depths and intervals, indicating 99.3°C. Seeds viability was determined using tetrazolium chloride (1% v/v). All recovered seeds were non-viable after soil sterilization.